2013
DOI: 10.4038/sljastats.v14i2.6221
|View full text |Cite
|
Sign up to set email alerts
|

Design of Exponentially Weighted Moving Average Scheme for Standardized Means

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Besides, Chang et al [20] designed the optimal EWMA chart in order to monitor the process variance shifts. In addition, Razmy [21] offered the EWMA chart the monitors the standardized process variance. Furthermore, Haq [22] proposed two auxiliary information-based charts, symbolized by AIBEWMA1 and AIBEWMA2 charts, that monitor the process variance efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Chang et al [20] designed the optimal EWMA chart in order to monitor the process variance shifts. In addition, Razmy [21] offered the EWMA chart the monitors the standardized process variance. Furthermore, Haq [22] proposed two auxiliary information-based charts, symbolized by AIBEWMA1 and AIBEWMA2 charts, that monitor the process variance efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…ey demonstrated that their control charts perform uniformly better against the control charts by Crowder and Hamilton [4] and Shu and Jiang [5]. Razmy and Peiris [12] designed an standardized EWMA control chart for monitoring of process dispersion. Later, Yang and Arnold [13] constructed an unbiased EWMA-p control chart for monitoring the process dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Roberts (1959) was the first person to introduce the exponentially weighted moving average (EWMA) control chart and since then, the EWMA control chart has been well accepted and widely used by practitioners. The EWMA chart is good for detecting small process shifts (Razmy & Peiris 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Shu (2008) extended the adaptive EWMA chart for process location to monitor the process dispersion. Razmy and Peiris (2013) designed the EWMA chart for monitoring standardized process variance.…”
Section: Introductionmentioning
confidence: 99%